2004
DOI: 10.1097/00004872-200403000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Relation between exercise-induced hypertension and sustained hypertension in adult patients after successful repair of aortic coarctation

Abstract: In adult post-coarctectomy patients, maximal exercise systolic blood pressure is independently associated with mean daytime systolic blood pressure at ambulatory blood pressure monitoring. In this study no independent predictive value of maximal exercise systolic blood pressure for left ventricular mass could be demonstrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
32
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(35 citation statements)
references
References 37 publications
3
32
0
Order By: Relevance
“…The clear association between exercise systolic blood pressure and systolic ambulatory blood pressure in our study (Vriend et al 2004b), suggest that post-coarctectomy patients with exercise-induced hypertension might also be at increased risk of future sustained hypertension. The increased carotid intima-media thickness is probably both cause and result of the higher ambulatory blood pressures found in these patients (Vriend et al 2004a).…”
Section: Sirssupporting
confidence: 48%
See 1 more Smart Citation
“…The clear association between exercise systolic blood pressure and systolic ambulatory blood pressure in our study (Vriend et al 2004b), suggest that post-coarctectomy patients with exercise-induced hypertension might also be at increased risk of future sustained hypertension. The increased carotid intima-media thickness is probably both cause and result of the higher ambulatory blood pressures found in these patients (Vriend et al 2004a).…”
Section: Sirssupporting
confidence: 48%
“…This result is in contrast with a recent study of our group. We found that maximal exercise systolic blood pressure and resting systolic blood pressure measured by conventional sphygmomanometry in 144 successfully repaired post-coarctectomy patients were both strong and independent predictors of mean daytime systolic blood pressure at ambulatory blood pressure monitoring (Vriend et al 2004b).…”
Section: Sirsmentioning
confidence: 82%
“…Indeed exercise-induced hypertension is thought to predict the onset of established hypertension, and is therefore considered important in the overall assessment of this patient group. 39,40 It is possible that the increases in cardiac output, seen with exercise, ejected into a less compliant aorta lead to significant increases in systolic blood pressure, which normalizes when cardiac output returns to normal. Further aortic remodeling and stiffening induced by continuing low velocity shear may lead to changes in baroreceptor sensitivity and progression toward established hypertension.…”
Section: Treatmentmentioning
confidence: 99%
“…There is a relationship between exercise-induced hypertension and sustained hypertension in adults with aortic coarctation [14]. Recently, Luijendijk et al demonstrated that peak exercise systolic blood pressure (SBP) is predictive for the development of chronic hypertension [1].…”
Section: Introductionmentioning
confidence: 99%